Analysis of Confirmed Cases of Corona Virus Diseases (COVID-19) in Nepal - Upadhyay, Rajendra Pd. (Kalika Journal of Multidisciplinary Studies, 2021)
An outbreak of COVID-19 pandemic disease, caused by a novel coronavirus SARS-coV-2, has posed a serious threat to global human health and economic activities. Nepal is also severely affected by this viral disease. The first case of COVID-19 patient was detected in Nepal on January 23, 2020. Since then, a total of 976,105 cases were reported as COVID-19 infected and the recovered cases were 953,430 with a recovery rate of 97.7 per cent with 11,928 deaths and a case fatality rate of 1.2 per cent until February 22, 2022. It would help the government to manage this crisis if the proper mechanism to predict COVID-19 cases has been developed. To combat COVID-19, the government of Nepal has taken various steps viz. diagnosis of the suspected cases, quarantine for people coming from other countries and isolation of the infected patients, lockdown, closure of the international boarder, increase public awareness, enforced social distancing, in the first phase, the addition of ICU beds, ventilator, oxygen concentrator and oxygen plant in a different hospital in the second phase and then vaccination of the target population, booster dose after the sixth month of a full dose of vaccination. This study aims to analyze the pattern of COVID-19 cases and death cases and forecast their values based on the data from January 23, 2020, to February 22, 2022, obtained from the website World Bank based on the ARMA model. This study indicates that the patients of COVID-19 are crossed three waves in Nepal, in the first wave the maximum number of cases was 4187, in second-wave the maximum number of cases was 9226 due to delta variant and in the third wave the maximum number of cases were 10052 is due to omicron. The forecasted value for March 18, 2022 for total cases is 984,595 with UCL values 1,056,143 and LCL values 913,047. Similarly, the forecasted value for new cases is 146 with UCL values 4,222 and LCL values 0 and for new death, the forecasted value is 4 with UCL values 78 and LCL values 0. These forecasted values indicate that the impact of Covid-19 is decreased rapidly due to vaccinations.